The Influence of Idealized Influence, Inspirational Motivation, Intellectual Stimulation and Individualized Consideration on Teaching Behavior Mediated by Entrepreneurial Behavior - Rini Puspitawati; Ricky Ricky (Petra International Journal of Business Studies, 2024)
The COVID-19 pandemic has highlighted numerous inequities within the education system, underscoring school leaders' need for strategic adjustments to enhance teacher competence for adaptive and effective teaching. This study investigates how transformational leadership influences teachers' instructional and entrepreneurial behaviors in the context of pandemic-era education. A quantitative research approach was employed, utilizing a 44-item questionnaire distributed to teachers to assess principal leadership, entrepreneurial behavior, and instructional practices. Findings indicate that principal leadership does not directly impact teachers' instructional behavior; instead, it influences their entrepreneurial behavior, which mediates the relationship between transformational leadership and instructional behavior. This research provides insights into the role of transformational leadership among school principals at the preschool and elementary levels within the framework of online education during the COVID-19 pandemic. Future studies are encouraged to incorporate a broader range of literature, as transformational leadership holds relevance across various institutional, organizational, and business contexts.